Measurement Scale for Consumers' Hedonic Values - a Comparison of Reliability Techniquesi - Tarka, Piotr (Skala do pomiaru wartości hedonistycznych konsumentów - analiza porównawcza różnych technik oceny rzetelnośc, 2010)
The main objective of this study is to explore a set of different value-items (indirectly observable variables, considered by young consumers) and transpose them according to statistical reliability rules into a single latent coherent scale dimension. Six items prepared and designed in the self-explanatory questionnaire were handed out to students at Polish and Dutch Universities across all classes. After collecting the answers from respondents and running in-depth reliability analysis based on various techniques of reliability testing, the author generated one scale being classified on the basis of items structure and their consistency. Different techniques of reliability assessment helped in this case to define the final resolution of the measurement and gave a description how small differences could exist among all of them.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 141, s. 105-114
Keywords: reliability; assessment techniques; scales; youth values and items configuration